(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The physico-chemical properties of the extracted oil were studied by the conventional methods. It was observed that Siyal Kanta grown under the soil and climatic condition of Bangladesh contains about 35% of pale yellow coloured oil. The total lipids were fractionated into three major lipid groups, neutral lipids, glycolipid and phospholipids by silicic acid column chromatography. Among the lipids, the neutral lipids were varied from 92.1-92.3%, glycolipid 5.5-5.8% and phospholipid 1.5-1.7% of the total oil of the lipid applied. The oil was also fractionated into mono-, di- and triglyceride by silicic acid column chromatography. The triglycerides were varied from 90.1-90.3%, diglycerides from 2.3-2.8% and monoglycerides from 1.5-1.8%. The saturated and unsaturated fatty acids present in the oil were separated and found to be 14.2-14.5% and 84.2-84.8% respectively depending on the areas in which the plant grows. The fatty acid compositions of the oil were analyzed by Gas Liquid Chromatography (GLC). The major fatty acids found in the oil were oleic acid (23%), linoleic acid (58%), palmetic acid (7%) and ricinoleic acid (10%). Key words: Siyal kanta seed oil; Glyceride; Lipid; Fatty acid. DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9607 BJSIR 2011; 46(4): 561-564